PENGARUH MARKETING EXPERIENCE DAN CUSTOMER VALUE TERHADAP KEPUASAN KONSUMEN PADA PT. INTAN NIRWANA NUSANTARA - Ambo Uleng; Mukhtar Tompo (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
This study aims to evaluate the influence of Marketing Experience on consumer satisfaction at PT. Intan Nirwana Nusantara and the influence of Customer value on consumer satisfaction at PT. Intan Nirwana Nusantara. This study is a study that uses a quantitative approach. With the data analysis method using descriptive statistics, data quality tests, simple linear analysis tests and hypothesis tests with the results of the study Marketing experience has no effect on consumer satisfaction at PT. Intan Nirwana Nusantara, Customer value has a positive and significant effect on consumer satisfaction at PT. Intan Nirwana Nusantara